2018
DOI: 10.1016/j.ejvs.2018.07.018
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Left Subclavian Artery Revascularisation in Thoracic Endovascular Aortic Repair: A Systematic Review and Meta-analysis

Abstract: The results of this review reveal that LSA revascularisation was associated with significantly lower peri-operative stroke and SCI rates. LSA revascularisation should be recommended for patients with LSA coverage in TEVAR. High quality RCTs are needed to further validate the conclusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(24 citation statements)
references
References 29 publications
0
17
0
Order By: Relevance
“… 22) A meta-analysis of 16 cohort studies with 2591 zone 2 TEVAR patients found that LSA revascularization was associated with a significantly lower perioperative spinal cord ischemia rate and stroke rate, so it is recommended in this review that LSA-covered patients should be considered for revascularization for the duration of TEVAR. 23) However, others reported that LSA revascularization was associated with an increased risk of aortic events or worse clinical outcomes compared with those without revascularization. 24 , 25) Balancing the pros and cons should be considered in individualized decision-making.…”
Section: Discussionmentioning
confidence: 99%
“… 22) A meta-analysis of 16 cohort studies with 2591 zone 2 TEVAR patients found that LSA revascularization was associated with a significantly lower perioperative spinal cord ischemia rate and stroke rate, so it is recommended in this review that LSA-covered patients should be considered for revascularization for the duration of TEVAR. 23) However, others reported that LSA revascularization was associated with an increased risk of aortic events or worse clinical outcomes compared with those without revascularization. 24 , 25) Balancing the pros and cons should be considered in individualized decision-making.…”
Section: Discussionmentioning
confidence: 99%
“…32 A Cochrane review concluded: “It is not possible to draw conclusions with regard to the optimal management of LSA coverage in TEVAR.” 23 A number of reviews on the need for LSA revascularization yield conflicting information possibly due to the retrospective nature of the studies where an unclear number of patients were revascularized selectively. 23,32-35…”
Section: Discussionmentioning
confidence: 99%
“…As a result of this and other studies, perioperative strokes of both techniques did not show a significant difference and were comparable to the reported 5.4% pooled stroke rate in a large meta-analysis of LSA revascularization and stroke as the primary outcome ( Table 4 ). 19) …”
Section: Discussionmentioning
confidence: 99%